Structural-linguistic approach to assessment of functional states of organism of elite sportsmen, who have symptoms of chronic tiredness - Abdulrahman, A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: assessment of functional states of sportsmen`s, having symptoms of chronic tiredness, organism with the help of structural-linguistic approach.